Mapping second messenger systems in the brain: differential localizations of adenylate cyclase and protein kinase C. - Worley, P F (1986)
[3H]Forskolin and [3H]phorbol 12,13-dibutyrate have been used to map the adenylate cyclase and phosphatidylinositol systems respectively in brain slices by light-microscopic autoradiography. [3H]Forskolin binding to brain sections is displaced potently by forskolin (KD approximately equal to 15 nM) and is enhanced by fluoride and GTP analogs, agents which activate the stimulatory GTP-binding regulatory protein of adenylate cyclase, Gs. Highest [3H]forskolin binding occurs in the corpus striatum, substantia nigra, hippocampus, and molecular layer of the cerebellum. Lesion studies demonstrate that binding sites in the substantia nigra are associated with striatal afferents, while hippocampal sites are localized to granule cell dendrites and mossy fiber terminals, and the intense binding in the cerebellar molecular layer is largely associated with granule cell axons and terminals. Protein kinase C mediates the activity of hormones and neurotransmitters, which act through the phosphatidylinositol cycle, and is labeled with high affinity by [3H]phorbol 12,13-dibutyrate. At many synapses, maps of adenylate cyclase and protein kinase C reveal reciprocal distributions, which may have implications for second messenger regulation of synaptic transmission.